#TITLE_ALTERNATIVE# - APRIANTI RIMADHANI AGUSTINI (NIM : 10107004); Pembimbing : Dr. Nuning Nuraini, DEVI
River pollution is one of the major environmental issues. The influence of river pollution are bioconcentration of contaminants on aquatic organisms such as fish and water quality degradation which are characterized by a decrease of dissolved oxygen concentration. At this final project there will be analyzed the bioconcentration of some contaminants in the fish as well as the influence of high concentrations of pollutants and the decrease in dissolved oxygen concentration in the Citarum River. Bioaccumulation model that used is a mathematical model that builds on mass balance concept. Bioconcentration pollutant model used is a mathematical model that builds on the concept of mass balance. While the model reduction of dissolved oxygen concentration, were analyzed based on the Streeter-Phelps model. The results of this final project in the form of a simulation performed with parameters adapted to the hydrological conditions of the Citarum River. It can be concluded that pollutans concentration in fish is much higher than pollutans concentration in water, especially for the type of organic pollutants. In addition, the decrease in dissolved oxygen concentration increases together with the increasing of organic pollutants concentration into the rivers.